Elevated body fat percentage is linked to increased risk of diabetes: a longitudinal retrospective cohort study based on Chinese adults - Pan, Weicong; Cai, Shichun; Huang, Zhenhua; Yu, Ke (Frontiers in Nutrition, 2025)
ObjectivePrevious studies have extensively explored the association between body mass index (BMI) and the risk of diabetes. However, evidence regarding the relationship between body fat percentage (BF%) and diabetes risk remained limited. This study aimed to investigate the association between BF% and the risk of diabetes among Chinese adults.MethodsWe conducted a retrospective cohort study involving 211,833 Chinese adults who underwent health evaluations from 2010 to 2016. The relationship between baseline BF% and diabetes risk was analyzed using Cox proportional hazards regression models. Additionally, cubic spline functions and smooth curve fitting were used to examine the nonlinear relationship between BF% and diabetes onset. Sensitivity and subgroup analyses were performed to validate the robustness of our findings.ResultsAfter adjusting for the variables, our analysis demonstrated that a 1% increase in BF% is associated with a 1.04-fold higher risk of diabetes (HR: 1.04, 95% CI: 1.04–1.05, p < 0.0001). Diabetes risk progressively increased across BF% quartiles (Q1 to Q4), with Q4 showing a significantly higher risk than Q1 (adjusted HR: 2.72, 95% CI: 2.19–3.37). Furthermore, a nonlinear association between BF% and diabetes risk was identified, with a critical inflection point at 25.09%. Below this threshold, the HR was 1.17 (95% CI: 1.13–1.21), while above it, the HR was 1.02 (95% CI: 1.02–1.03). The subgroup analysis and sensitivity analysis demonstrated the robustness of these results.ConclusionThis study indicates a positive, nonlinear relationship between BF% and diabetes risk in Chinese adults. Reducing BF% below the identified threshold could significantly lower the risk of developing diabetes.